2018
DOI: 10.1038/s41388-018-0181-8
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cyclin E1 attenuates hepatitis and hepatocarcinogenesis in a mouse model of chronic liver injury

Abstract: Chronic liver injury triggers liver fibrosis and hepatocellular carcinoma (HCC), the third leading cause of cancer-related mortality. Cyclin E1 (CcnE1, formerly designated Cyclin E) is a regulatory subunit of the Cyclin-dependent kinase 2 (CDK2). It is overexpressed in approximately 70% of human HCCs correlating with poor prognosis, while the relevance of its orthologue Cyclin E2 (CcnE2) is unclear. Hepatocyte-specific deletion of NF-kappa-B essential modulator (NEMO) leads to chronic hepatitis, liver fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In our present study, ablation of CcnE1 largely prevented the development of HCC in two independent tumor models, and previous analysis indicated that inhibition of CcnE1 may also attenuate hepatocarcinogenesis in an inflammatory environment (6). In sharp contrast, CcnE2 was fully dispensable for HCC formation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our present study, ablation of CcnE1 largely prevented the development of HCC in two independent tumor models, and previous analysis indicated that inhibition of CcnE1 may also attenuate hepatocarcinogenesis in an inflammatory environment (6). In sharp contrast, CcnE2 was fully dispensable for HCC formation.…”
Section: Discussionsupporting
confidence: 75%
“…These signatures are useful for predicting patient prognosis and for developing novel cyclin E-based HCC therapies. chronic hepatitis (6). Here, we aimed to genetically dissect the precise contribution of CcnE1, CcnE2, or Cdk2 for HCC initiation and/or progression.…”
Section: Significancementioning
confidence: 99%
“…Overexpression of the CCNE1 gene, which is correlated with poorer prognosis, is observed in around 70% of HCC patients. High levels of CCNE1 have recently been associated with a hepatic inflammatory response, liver disease progression and hepatocarcinogenesis (Ehedego et al, 2018). HBV mainly integrates into the promoter or introns of the CCNA2 gene and may lead to the expression of a chimeric HBV-human protein which was reported to deregulate cell cycle in liver cells (Chiu et al, 2016).…”
Section: Fusion Sites Within Hbv and The Human Genomementioning
confidence: 99%
“…19,20 CCNE1, a kind of cyclins, is required for cell cycle G1/S transition. 22 In spite of a study demonstrated that the down expression of CCNE1 reduced the liver tumorigenesis significantly in a mouse model, 23 the function of CCNE1 in human HCC is poorly understood. 22 In spite of a study demonstrated that the down expression of CCNE1 reduced the liver tumorigenesis significantly in a mouse model, 23 the function of CCNE1 in human HCC is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…21 The abnormal expression of CCNE1 was reported in ovarian cancer. 22 In spite of a study demonstrated that the down expression of CCNE1 reduced the liver tumorigenesis significantly in a mouse model, 23 the function of CCNE1 in human HCC is poorly understood.…”
Section: Introductionmentioning
confidence: 99%